2019
DOI: 10.1128/mra.01106-19
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Genome Assembly of a Plant-Associated Rhodococcus qingshengii Strain (RL1) Isolated from Eruca sativa Mill. and Showing Plant Growth-Promoting Properties

Abstract: Rhodococcus qingshengii RL1 was isolated from surface-sterilized leaves of Eruca sativa Mill. and shows plant growth-promoting (PGP) properties. The de novo genome assembly consists of one chromosome with 6,253,838 bp and two plasmids with 144,038 bp and 448,745 bp. Many genes could be identified reflecting its PGP potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…MS6 is similar to auxin it induces cell wall formation and promotes the growth of basal stem cells. Many other studies also have shown that Rhodobacteraceae promote plant growth (Stevens et al, 2017;Abraham and Silambarasan, 2018;Kuhl et al, 2019;Vergani et al, 2019). Ambient environmental parameters are another important factor affecting the abundance and diversity of microbial community on the surface of U. fasciata.…”
Section: Discussionmentioning
confidence: 96%
“…MS6 is similar to auxin it induces cell wall formation and promotes the growth of basal stem cells. Many other studies also have shown that Rhodobacteraceae promote plant growth (Stevens et al, 2017;Abraham and Silambarasan, 2018;Kuhl et al, 2019;Vergani et al, 2019). Ambient environmental parameters are another important factor affecting the abundance and diversity of microbial community on the surface of U. fasciata.…”
Section: Discussionmentioning
confidence: 96%
“…We also suggest that the R. erythropolis strains assigned to the R. qingshengii group should be re-named as previously recommended ( Sangal et al, 2016 ; Thompson et al, 2020 ). The genomes of RL1 and djl6 were clearly identified as belonging to the R. qingshengii cluster ( Xu et al, 2007 ; Kuhl et al, 2019 ) and had more genes in common with each other than with BG43 ( Figure 2 ), whereas the BG43 genome was classified as R. erythropolis ( Müller et al, 2014 ; Rückert et al, 2015 ). Despite the clear separation the strains RL1 and BG43 had many functional traits in common, indicating a close functional overlap between the species.…”
Section: Discussionmentioning
confidence: 99%
“…The genome of Rhodococcus qingshengii RL1 ( Kuhl et al, 2019 ) was compared to the genomes of the type strain Rhodococcus qingshengii djl6 ( Xu et al, 2007 ; Wang et al, 2010 ; Táncsics et al, 2014 ), as well as the closely related soil isolate Rhodococcus erythropolis BG43 ( Rückert et al, 2015 ). The genome djl6 is based on the species R. jialingiae ( Wang et al, 2010 ) which was later identified as a synonym of the type strain R. qingshengii ( Táncsics et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations